Description of two new species of Neotanais Beddard, 1886 (Crustacea, Tanaidacea) from KODOS area - Wi, Jin Hee; Suh, Hae Lip; Yu, Ok Hwan (Zootaxa, 2015)
Two new species of Neotanais Beddard, 1886 are described from the Korea Deep Ocean Study (KODOS) area in the Clarion–Clipperton Fracture Zone, based on the collections performed on board R/V Onnuri from a depth of 5180 m. Neotanais triqueturus n. sp. is similar to the ‘pfaffi group’ characterized by pereonites with a swollen distolateral margin, pleonites with mid-ventral spurs and tapered lateral margins but can be differentiated by a longer cephalothorax (length: width 1.6: 1), a cheliped with a large protrusion on the mid-dorsal margin of the fixed finger, and the presence of a ventral process on the cheliped carpus. Neotanais brevis n. sp. has the characteristics of the ‘micromopher’ group, with pleonites narrower than pereon, a cheliped carpus without a ventral process, and a uropod endopod with nine articles but can be differentiated by a combination of the pleonites without mid-ventral spurs, a relatively longer pleotelson (length: width 1: 1.5 vs. 1: 2), a uropod basis with one seta on each of the ventral and dorsal margins, and the cheliped fixed finger with proximal denticles. In this study, in order to prove N. triqueturus and N. brevis were new species, full descriptions and a comparison with the closely related species are given. In addition, comprehensive comparisons with the species of Neotanais from the east-central Pacific are tabulated and discussed.